A study on searching optimal path for robot using genetic algorithm - Park, So Young; Park, Pyoung Woo; Kim, Jung Min; Borm, Jin Hwan; Lee, Seok Won (Journal of the Korean Society for Precision Engineering, 2018)
This paper presents a search methodology for the optimal operational path of robots using a genetic algorithm. The work scheduled to be performed using a robot was characterized. Collision avoidance between the robot including the working tool and the target object was considered. In this study, we followed the general steps of data mining. We compared the time taken by the robot moving along the path created by our proposed methodology with the time taken for the robot along the path created by real humans. The results show that the path generated by this study was more efficient than that of humans.
Keywords: Genetic algorithm; Industrial robot; Optimal path; Path searching